An Investigation of Sociometric Status on Students’ Achievement in Indonesian EFL Speaking Class - SARLIN, Sarlin; ABDULLAH, Abdullah; BAKRI, Fitriyani; HASBI, Muhammad (Research and Innovation in Applied Linguistics, 2024)
The relationship among peers that occur in the teaching and learning process becomes essential to be investigated where it might influence students’ academic achievement. In depth, Sociometric Status is an indicator to categorize the relationship of individual among groups of friends whether he or she is liked or disliked by his or her peers. The purpose of this study is to investigate sociometric status on students’ achievement especially in the speaking skill. Thirty students at the twelfth grade of social science class are study consists of observation checklist, rating-scale measurement, and students speaking score. Observation checklist is used to observe students’ behaviors with their peers during the teaching process and rating scale measurement is given to students before conducted observation. In addition, students speaking score is collected through the result of students speaking test after doing observation. The result of this study indicates positive and negative influence of the sociometric status on the students’ achievement. This study is hoped to give beneficial contribution about how the sociometric status of the students affects their achievement in EFL speaking class. Therefore, teacher would be able to do appropriate treatment to help students overcome their psychological problems and also to make the good atmosphere among the students in the speaking class.